European Union law’s proximity to citizens through education and the use of digital technologies - Silva, Maria Manuela Magalhães (2020)
Education forms the basis for active citizenship. The integration model followed in the construction of the European Union (EU) includes the action of its institutions, which develop competencies and lines of implementation through legislative, decision-making and sanctionary paths. All procedures involved result in the preparation of documents. The use of technology has extended access, giving these digital media a legal category as a source of law; today available on the e-mail address or in the EU's own publications; of access to interested specialists or to the general public, being in the interest of citizens, academics or institutions. Differentiated levels of access are created, which is not unrelated to the degree of digital literacy. The European Union is a union of common values and is based on the values of democracy, defense of human rights and the rule of law and, as such, with a strong component of creation and respect for legal standards. Concerns about the transparency of procedures and accessibility are real, but not always completely effective. Education is one of the keys to the future and can and must be part of the solution to solving problems such as, in this case, accessibility to information on European Union law. The chosen theme concerns the effective application of EU rules as an important aspect for European citizens that affects their daily lives and how citizens feel the closeness to EU law. As the problem is not always the absence of EU legislation, but rather the fact that such legislation can be known and applied effectively. The implementation of EU law is a challenge that requires a greater emphasis on enforcement to serve the general interest. And what role does education and the use of digital technologies play in this context? How can investment in education considering new technologies bring citizens closer to the functioning of the EU? Will this lead to a strengthening of democracy? The aim of this analysis is to demonstrate that, as the Member States are primarily responsible for the application of EU law, there is still a way to achieve more efficiency in the application of European legislation, which implies, on the part of States, public policies aimed at education and training on new technologies that may be an instrument to motivate and increase knowledge of said legislation, which in turn will allow a more effective exercise of active citizenship. Considering the embryonic nature of this study, a methodology was designed that focuses on the use of European Union law sources, through systematic and methodologically selected normative interpretation. It focuses on specialized publications and above all official documents (legislative or preparatory) that enshrine the issue. The theoretical-academic focus is consolidated through systematic normative interpretation and aims to expand knowledge, in a qualitative and exploratory approach. Without presenting quantitative data, the purpose is to bring to discussion and debate the role, value, education capacity and ability of using new technologies for the dissemination and application of European Community law.